2021
DOI: 10.3390/life11101029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Future Prospects of Immunotherapy in Lung Cancer

Abstract: The three major conventional treatments: surgery, chemotherapy, and radiation therapy, have been commonly performed for lung cancer. However, lung cancer is still the leading cause of cancer-related mortality. Immunotherapy has recently emerged as a very effective new treatment modality, and there is now growing enthusiasm for cancer immunotherapy worldwide. However, the results of clinical studies using immunotherapy are not always favorable. Understanding the steps involved in the recognition and eradication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 145 publications
(160 reference statements)
0
9
0
Order By: Relevance
“…However, their efficiency in monotherapy is still limited to 10–20% of unselected patients ( Hellmann et al, 2019 ; Herbst et al, 2020 ; Reck et al, 2016 ), and some initial responders eventually develop resistance. Therefore, combination therapies and optimization of sensitivity or resistance predictive biomarkers are emerging to further improve the efficacy of immunotherapy treatments (reviewed in Kinoshita et al [2021] and Grant et al [2021] ).…”
Section: Introductionmentioning
confidence: 99%
“…However, their efficiency in monotherapy is still limited to 10–20% of unselected patients ( Hellmann et al, 2019 ; Herbst et al, 2020 ; Reck et al, 2016 ), and some initial responders eventually develop resistance. Therefore, combination therapies and optimization of sensitivity or resistance predictive biomarkers are emerging to further improve the efficacy of immunotherapy treatments (reviewed in Kinoshita et al [2021] and Grant et al [2021] ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in clinical trials, cancer vaccines have not shown a positive effect on the survival of patients with NSCLC. On the other hand, conflicting data have been obtained on the effects of cytokine therapy on prognosis in lung cancer [ 21 , 22 ]. Immune checkpoint inhibitors are widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors are widely used in clinical practice. Thus, nivolumab, ipilimumab, and pembrolizumab are used in the complex therapy of lung cancer [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapies such as immune checkpoint inhibitors have proved to be highly effective in clinical trials. Nonetheless, many patients receiving immunotherapy will still develop immune resistance [ 5 ]. Intratumoral heterogeneity compromises the clinical efficacy of anticancer drugs, for instance, in the case of immunotherapy in cancer.…”
Section: Introductionmentioning
confidence: 99%